2016
DOI: 10.1002/jso.24342
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of vascularized versus non‐vascularized lymph node transplant in animal models for lymphedema. Review of the literature

Abstract: Lymph node transfer has been performed to treat lymphedema for several years. The goal of this procedure is to provide a bridge between the lymphatic system distal and proximal to the lymph node dissection. There is a lack of consensus about the necessity of an additional vascular anastomosis for the transplanted lymph nodes. A systematic literature search in Cochrane Library database CENTRAL, MEDLINE, and EMBASE of animal studies using lymph node transplantation with and without additional vascularization was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Maintaining the vascular supply to the transferred lymph nodes is important for survival and preservation of function (Shesol et al, ; Uygur et al, ). However, experimental studies comparing vascularized and nonvascularized lymph node transfer are still lacking in the literature (Cornelissen et al, ; Tobbia, Semple, Baker, Dumont, & Johnston, ). Moreover, the immunologic activity and function of the transferred lymph nodes has not been sufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining the vascular supply to the transferred lymph nodes is important for survival and preservation of function (Shesol et al, ; Uygur et al, ). However, experimental studies comparing vascularized and nonvascularized lymph node transfer are still lacking in the literature (Cornelissen et al, ; Tobbia, Semple, Baker, Dumont, & Johnston, ). Moreover, the immunologic activity and function of the transferred lymph nodes has not been sufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several small and large animal models of lymph node transfer have been reported to date (Cornelissen et al, ). In most cases, however, lymph nodes were transferred as nonvascularized free grafts with (Shioya et al, ; Tammela et al, ) or without (Aschen et al, ) fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the mouse model is actually a particularly useful model with which to specifically study lymphangiogenesis independent of revascularization. Of note, multiple studies in larger animal models such as sheep, dogs, and pigs have shown that revascularization increases lymph node survival and lymphatic function [18, 47]. However, many of these studies utilized models of lymphatic injury that do not correlate to the clinical scenario as well as our lymphatic ablation model.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these studies utilized models of lymphatic injury that do not correlate to the clinical scenario as well as our lymphatic ablation model. In addition, some of these studies are limited by the absence of clinical lymphedema prior to transplantation, so the results may be confounded with less applicable clinical translation [47]. Therefore, although clinical studies provide evidence for the benefit of revascularization, future studies in larger animal models that closely simulate lymphedema are necessary to understand the cellular mechanisms underlying the effect of vascularized LNT on lymphatic function [12].…”
Section: Discussionmentioning
confidence: 99%
“…have reported promising outcomes in the clinical setting . There is also considerable evidence from animal models showing the effectiveness of LN transplantation . However, this technique is still in the exploratory stages and there is no direct evidence of how LN transplantation acts on the lymphatic system, so its effect on immunity in particular is still unclear.…”
Section: Introductionmentioning
confidence: 99%